RESEARCH OF THE POSSIBILITIES OF AUTOMATION OF ACCOUNTING IN THE ARMED FORCES OF UKRAINE - ORLOVSKYI, SERHII; STATSENKO, DMYTRO (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The paper presents a comparative analysis of the existing methods of property accounting in the Armed Forces of Ukraine, the main advantages and disadvantages of each of them, namely, paper-based accounting and spreadsheet accounting. The author considers accounting as a system of interrelated elements that interact with each other and form a single whole. The author identifies the existing problems with property accounting in the Armed Forces of Ukraine, which do not meet modern technologies and are very time-consuming. Also, one of the main problems is the problem of protection against unauthorized access. The existing solution to the problem of property accounting using the SAP R/3 ERP system is considered. The use of ERP systems will significantly reduce time costs, obtain reliable information on the status of resources and materials for strategic planning and management forecasts. The article highlights the disadvantages of the SAP system itself, such as vendor dependence, complexity of transition and the need for constant improvement of new modules. It is also worth noting the lack of scalability. That is, it will not be sufficiently functional for the armed forces, as the armed forces are also a huge system with their own internal subsystems, and therefore certain modules and algorithms will have to be constantly modified. The complexity of the transition to ERP systems and the constant need for qualified personnel stand out. The practical significance is to increase the efficiency of property accounting in the Armed Forces of Ukraine, simplify document management using existing web applications such as ARMY+. A solution is proposed that will reduce dependence on the developer company and reduce the need for constant revision of new modules. The ways to implement the transition to modern ERP systems are highlighted. Also, the domestic ERP system will allow to control data servers and will be simple and understandable for the Ukrainian user.